Ways to improve the effectiveness of tourist training grounds on the terrain in the ‘distance-walking’ discipline group - Nabiullin, R.R.; Zakirov, N.N.; Nabiullin, A.R. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to design a tourist training ground taking into account the characteristics of the terrain and to justify its operational potential in the system of additional education for young tourists. Methods and structure of the study. Comparative analysis of classic tourist training grounds; a training ground was created in the village of Siza (Arsky District, Tatarstan) using the design method. Results and conclusions. An innovative, practice-oriented model of a tourist training ground is presented, distinguished by its versatility, accessibility, multifunctionality, and organic integration with the natural landscape. 7 key advantages are highlighted and justified. This methodology brings training closer to real camping conditions, forming sustainable practical skills, and can be used in tourist and local history clubs, sections, and camps.